Revision of the Paleartic species of the genus Ochthebius Leach (Coleoptera: Hydraenidae) XXIV. Description of Ochthebius (Asiobates) sanabrensis n. sp. from northwestern Spain - Valladares, Luis F.; Jäch, Manfred A. (Zootaxa, 2008)
In the Palearctic region, the hydraenid subgenus Asiobates Thomson, 1859 comprises two species groups (Jäch, 1990): the O. minimus Fabricius group and the O. bicolon Germar group. The O. bicolon group is quite diverse in the Iberian Peninsula (12 species) displaying a high level of endemism (six Iberian endemic species). In contrast, only two Iberian species of the O. minimus group are known to date, with both rather widely distributed in the western Palearctic Region: O. (Asiobates) aeneus Stephens, 1835 and O. (A.) minimus (Fabricius, 1792). A new species, apparently endemic to the northwestern Iberian Peninsula, is now added to this group.